Adverse childhood experiences and health risk behaviours among the undergraduate health campus students - Majid, Mardhiah (2022)
Adverse childhood experiences (ACEs) have been shown to be linked with health risk behaviors (HRBs). The aim of this study is to evaluate ACEs among the undergraduate Health Campus of a university in the northeast of Malaysia, and the associated health risk behaviors. This cross-sectional study performed by recruiting 973 undergraduate students at the Health Campus of a public university from December 2019 to June 2021. An anonymous, self-reported questionnaire which consisted of the World Health Organization ACE-International Questionnaire and The Youth Risk Behavior Surveillance System (YRBSS) were distributed randomly to students according to the course and year of study by hard copies or via online questionnaires. This study found that ACEs were highly reported among participating university students ranging from 2.6 to 39.3%. The most commonly reported adversities were: emotional abuse (30.2%), emotional neglect (29.2%) and physical abuse (28.7%). The incidence of community violence was high, with about 39.3% of survey participants reporting the experience. The highest incidence of HRBs among respondents was 54.5% from physical inactivity, followed by overweight/obesity (28.8%) and safety negligence included text/email during driving (20.6%). The findings of this study showed that those who were exposed to ACEs were at risk of HRBs, for example participants with history of emotional neglect were more likely to have sexual risk behavior (AOR = 2.26, 95% CI 1.040 – 4.911). This study also supported that higher number of ACEs were associated with higher number of HRBs. Thus, the study has provided evidence on child maltreatment as one of the important public health problems in Malaysia.